Role of Hepatic Resection for HCC in the era of Transplantation; an Experience of Two Tertiary Egyptian Centers - Senbel, Ahhmed (Indian J Surg Oncol, 2017)
The surgical treatments of hepatocellular carcinoma (HCC) in a cirrhotic liver include both hepatic resection and liver transplant. While the liver transplant is considered as a golden therapy, it has some obstacles including shortage of organs especially living donors, economic circumstances, and the progression of a tumor while waiting for the transplant so the second choice which is resection should have a role. In this study, 84 patients with HCC (who were legible for transplant according to Milan and extended selection criteria) were enrolled for hepatic resection. The outcome including complication and the oncologic outcome was evaluated. We followed our patients for 15 months as a median follow-up (range from 3 to 50 months); we noticed 10 tumor relapse (11.7%) and seven lost (8.3%). We also noticed no recurrence. Patients’ overall survival showed a median of 15 and 50 months, respectively. We can conclude that there is reasonability for HR as an effective optional treatment for patients with HCC who are legible for transplant particularly for patients with a Child-A scoring.